2018
DOI: 10.2478/pjct-2018-0040
|View full text |Cite
|
Sign up to set email alerts
|

Water Demineralization by Membrane Distillation Utilizing Cooling Water From Municipal Waste Incinerator

Abstract: The membrane distillation performance was studied for production of demineralized water from surface water (river). Hot water from cooling water system of municipal waste incinerator was considered as an energy source for membrane distillation. The integration of membrane installation with such cooling water system allows to re-use up to 18 kW per 1 m2 of the membranes. The studies were performed with the application of polypropylene capillary membranes Accurel PP S6/2. The membrane modules were supplied with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…By comparing the three technologies of distillation, electrodialysis and reverse osmosis membrane (RO) technology to treat high-mineralization mine water, it has been found that the effluent water quality of the distillation method is good, and it can be obtained in the specific environment of low-cost heat sources near the coal mine; RO has comprehensive advantages in effluent quality, power consumption, desalination efficiency, floor space, and degree of automation [2]. Membrane distillation (MD) is a separation process combining membrane technology and distillation, and has unique advantages in the field of high-salt wastewater treatment [3]. For concentrated water after the RO treatment, the MD process is used, and the performance of the new hydrophobic composite membrane is optimized by the coating method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the three technologies of distillation, electrodialysis and reverse osmosis membrane (RO) technology to treat high-mineralization mine water, it has been found that the effluent water quality of the distillation method is good, and it can be obtained in the specific environment of low-cost heat sources near the coal mine; RO has comprehensive advantages in effluent quality, power consumption, desalination efficiency, floor space, and degree of automation [2]. Membrane distillation (MD) is a separation process combining membrane technology and distillation, and has unique advantages in the field of high-salt wastewater treatment [3]. For concentrated water after the RO treatment, the MD process is used, and the performance of the new hydrophobic composite membrane is optimized by the coating method.…”
Section: Introductionmentioning
confidence: 99%
“…TRNSYS 17.2 software has been used to simulate the solar-driven membrane distillation system [13]. The system set the effective area of the collector to 22.6 m 2 , the membrane surface area to 7.2 m 2 , and the initial water volume of the feed tank to 3m 3 . Hourly weather data was used as meteorological input data, and the running time was 5 days.…”
Section: Introductionmentioning
confidence: 99%